A new genus, with a new species, from Brazil (Acari: Prostigmata: Cunaxidae) - De Castro, Tatiane Marie Martins Gomes [UNESP]; Den Heyer, Jacob (Magnolia Press, 2008)
A new cunaxid genus from Brazil, Cunaxatricha gen. nov., is erected and its type species, Cunaxatricha tarsospinosa sp. nov. is described and figured. A key to the genera of the subfamily Cunaxinae, to which this new genus belongs, is provided. Copyright © 2008 Magnolia Press.
Keywords: Bdelloidea; Cunaxinae; Identification key; Predatory mite; Taxonomy